Pathological Ventricular Remodeling: Mechanisms: Part 1 of 2 - Burchfield, Jana S.; Xie, Min; Hill, Joseph A. (Circulation (New York, N.Y.), 2013)
Despite declines in heart failure morbidity and mortality with current therapies, rehospitalization rates remain distressingly high, substantially affecting individuals, society, and the economy. As a result, the need for new therapeutic advances and novel medical devices is urgent. Disease-related left ventricular remodeling is a complex process involving cardiac myocyte growth and death, vascular rarefaction, fibrosis, inflammation, and electrophysiological remodeling. Because these events are highly interrelated, targeting a single molecule or process may not be sufficient. Here, we review molecular and cellular mechanisms governing pathological ventricular remodeling.